Late Neogene tectonically driven crustal exhumation of the Sikkim Himalaya: Insights from inversion of multithermochronologic data. Issue 3 (30th March 2016) - Landry, Kyle R.; Coutand, Isabelle; Whipp, David M.; Grujic, Djordje; Hourigan, Jeremy K.
Abstract: Apatite fission track and zircon (U‐Th)/He data are reported for 34 bedrock samples distributed between the foothills and the topographic crest of the Darjeeling‐Sikkim Himalaya. The pattern of observed cooling ages does not correlate with topography, rainfall distribution, and the deeply incised high‐relief Tista window, indicating that tectonic processes are mainly responsible for their spatial distribution. Inversion of this thermochronometric data set using 3‐D thermokinematic modeling constrained by independent geological and geophysical observations was performed to evaluate the contribution of slip partitioning, duplex development, and relief growth on the evolution of the thermal structure of the Himalaya during the last 12 Ma. Models involving significant relief growth do not show a substantial influence of topography evolution on the cooling age distribution, while models involving duplex growth demonstrate that tectonic processes exert a dominant influence on their distribution. In concert with equivalent studies in Bhutan, central Nepal, and NW India, our results attest that the lateral variation of the geometry and kinematics of the Himalayan basal décollement locally associated with duplex formation exert a leading influence on lateral variations of middle to upper crustal long‐term exhumation rates documented along the strike of the Himalaya. Key Points: Thermochronological data are insensitive to relief changes in fast‐eroding Himalaya Late Neogene tectonics of Sikkim is dominated by duplex formation Late Neogene exhumation of the Himalaya is driven by tectonic processes